Sin^4x -cos^4x= cos3x Could you solve this?

4 Answers
Apr 5, 2018

x= pi/5 x=π5
x = (3pi)/5 x=3π5
x= pix=π

Explanation:

We have:

(sin^2x+ cos^2x)(sin^2x- cos^2x) = cos(3x)(sin2x+cos2x)(sin2xcos2x)=cos(3x)

1(sin^2x - cos^2x)= cos(3x)1(sin2xcos2x)=cos(3x)

-cos(2x) = cos(3x)cos(2x)=cos(3x)

0 = cos(3x) + cos(2x)0=cos(3x)+cos(2x)

0 = cos(2x)cos(x) - sin(2x)sinx + cos(2x)0=cos(2x)cos(x)sin(2x)sinx+cos(2x)

0 = (2cos^2x -1)cosx- 2sinxcosxsinx + 2cos^2x- 10=(2cos2x1)cosx2sinxcosxsinx+2cos2x1

0 = 2cos^3x - cosx - 2sin^2xcosx + 2cos^2x - 10=2cos3xcosx2sin2xcosx+2cos2x1

0 = 2cos^3x- cosx - 2(1- cos^2x)cosx + 2cos^2x - 10=2cos3xcosx2(1cos2x)cosx+2cos2x1

0 = 2cos^3x- cosx - 2(cosx - cos^3x) + 2cos^2x- 10=2cos3xcosx2(cosxcos3x)+2cos2x1

0 = 2cos^3x- cosx- 2cosx+ 2cos^3x +2cos^2x- 10=2cos3xcosx2cosx+2cos3x+2cos2x1

0 = 4cos^3x + 2cos^2x - 3cosx -10=4cos3x+2cos2x3cosx1

Let u = cosxu=cosx.

0 = 4u^3 + 2u^2 - 3u - 10=4u3+2u23u1

We see that u = -1u=1 is a factor. Using synthetic division we get

0 = (x + 1)(4x^2 - 2x - 1)0=(x+1)(4x22x1)

The equation 4x^2 - 2x - 1= 0 4x22x1=0 may be solved using the quadratic formula.

x = (2 +- sqrt(2^2 - 4 * 4 * -1))/(2 * 4)x=2±2244124

x = (2 +- sqrt(20))/8x=2±208

x = (1 +- sqrt(5))/4x=1±54

x ~~ 0.809 or -0.309x0.809or0.309

Since cosx = ucosx=u, we get x = pi/5, (3pi)/5x=π5,3π5 and piπ.
Where nn is an integer.

The graph of y_1 = sin^4x- cos^4xy1=sin4xcos4x and y_2 = cos(3x)y2=cos(3x) confirms that the solutions are the intersection points.

enter image source here

Hopefully this helps!

Apr 5, 2018

x = (2k + 1)pix=(2k+1)π
x = ((2k - 1)pi)/5x=(2k1)π5

Explanation:

sin^4x - cos^4 x = cos 3xsin4xcos4x=cos3x
(sin^2 x + cos^2 x)(sin^2 x - cos^2 x) = cos 3x(sin2x+cos2x)(sin2xcos2x)=cos3x
1(sin^2 x - cos^2 x) = cos 3x1(sin2xcos2x)=cos3x
-cos 2x = cos 3xcos2x=cos3x, or
cos 3x = - cos 2x = cos (2x + pi)cos3x=cos2x=cos(2x+π)
Unit circle, and property of cos, give -->
3x = +- (2x + pi) + 2kpi3x=±(2x+π)+2kπ
a. 3x = 2x + pi + 2kpi3x=2x+π+2kπ
x = (2k + 1)pix=(2k+1)π
If k = 0 --> x = pix=π
b. 3x = - 2x - pi + 2kpi3x=2xπ+2kπ
5x = (2k - 1)pi5x=(2k1)π,
x = ((2k - 1)pi)/5x=(2k1)π5
If k = 1 --> x = pi/5x=π5.
If k = 0 --> x = - pi/5x=π5, or x = (9pi)/5x=9π5 (co-terminal)
If k = 2 --> x = (3pi)/5x=3π5
In the closed interval [0, 2pi], the answers are:
0, (pi)/5, (3pi)/5, pi, (9pi)/50,π5,3π5,π,9π5
Check by calculator.
x = pi/5 = 36^@x=π5=36 --> sin^4 x = 0.119sin4x=0.119 --> cos^4 x = - 0.428cos4x=0.428 --> cos 3x = - 309.
sin^4 x - cos^4 x = 0.119 - 0.428 = - 309sin4xcos4x=0.1190.428=309 . Proved
x = (9pi)/5x=9π5 --> sin^4 x = 0.119sin4x=0.119 --> cos^4 x = 0.428cos4x=0.428 -->
sin^4 x - cos^4 x = - 0.309sin4xcos4x=0.309
cos 3x = cos 972 = - 0.309cos3x=cos972=0.309. Proved

Apr 13, 2018

rarrx=(2n+1)pi/5, (2n+1)pi x=(2n+1)π5,(2n+1)π nrarrZnZ

Explanation:

rarrsin^4x-cos^4x=cos3xsin4xcos4x=cos3x

rarr(sin^2x+cos^2x)(sin^2x-cos^2x)=cos3x(sin2x+cos2x)(sin2xcos2x)=cos3x

rarr-cos2x=cos3xcos2x=cos3x

rarrcos3x+cos2x=0cos3x+cos2x=0

rarr2cos((3x+2x)/2))*cos((3x-2x)/2))=02cos(3x+2x2))cos(3x2x2))=0

rarrcos((5x)/2)*cos(x/2)=0cos(5x2)cos(x2)=0

Either cos((5x)/2)=0cos(5x2)=0

rarr(5x)/2=(2n+1)pi/25x2=(2n+1)π2

rarrx=(2n+1)pi/5x=(2n+1)π5 nrarrZnZ

rarrcos(x/2)=0cos(x2)=0

rarrx/2=(2n+1)pi/2x2=(2n+1)π2

rarrx=(2n+1)pix=(2n+1)π nrarrn

Apr 29, 2018

The general solution doesn't require the triple angle formula, and is

x=180 ^circ + 360^circ kx=180+360k or x = 36^circ + 72^circ kx=36+72k

for integer kk.

Explanation:

I don't like reading other people's answers before I solve a question myself. But a featured answer for this one popped up. During my quick glance I couln't help notice it looked pretty complicated for what looks to me like a relatively easy question. I'll give it a shot.

sin ^4 x - cos ^4 x = cos 3x sin4xcos4x=cos3x

(sin ^2 x + cos ^2 x)(sin ^2 x - cos ^2 x ) = cos 3x (sin2x+cos2x)(sin2xcos2x)=cos3x

-cos 2x = cos 3x cos2x=cos3x

cos (180^circ - 2x) = cos 3x cos(1802x)=cos3x

I've been on Socratic for a couple of weeks, and this is emerging as my theme: The general solution to cos x = cos acosx=cosa is x = \pm a + 360 ^circ k quad for integer k.

180^circ - 2x = \pm 3x + 360^circ k

-2x \pm 3x = -180^circ + 360^circ k

We take the signs separately. Plus first:

x = -180^circ + 360^circ k = 180 ^circ + 360^circ k

Minus next.

-5x = -180^circ + 360^circ k

x = 36^circ + 72^circ k

If you read these closely you might think I'm making a mistake with the way I manipulate k. But since k ranges over all the integers, substitutions like k to -k and k to k+1 are allowed and I slip those in to keep the signs + when they can be.

Check:

Let's pick a couple to check. I'm geeky enough to know cos 36^circ is half the Golden Ratio, but I'm not going to work these out exactly, just pop them into Wolfram Alpha to make sure.

x = 36^circ + 72^circ = 108^circ

sin ^4 108 - cos ^4 108 - cos (3 * 108) = 0 quad sqrt

x = 180 - 2 (360) = -540

sin ^4 (-540) - cos^4(-540) - cos(3 * -540) = 0 quad sqrt